2014
DOI: 10.3342/ceo.2014.7.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clonidine and Midazolam Premedication Before Endoscopic Sinus Surgery: Results of Clinical Trial

Abstract: ObjectivesPremedication with clonidine has been found to reduce the bleeding during endoscopic sinus surgery (ESS), therefore lowering the risk of surgical complications. Premedication is an essential part of pre-surgical care and can potentially affect magnitude of systemic stress response to a surgical procedure. The aim of this study was to compare the efficacy of premedication with clonidine and midazolam in patients undergoing sinus surgery.MethodsForty-four patients undergoing ESS for chronic sinusitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a similar 2005 study, Pena et al studied prior endoscopic procedures, history of drug and alcohol use, and nervousness before procedure to predict adverse endoscopic experiences [ 11 ]; similar to Bal et al [ 10 ], they found nervousness and psychotropic drug use to be significantly associated with adverse events. Other interesting patient factors that have been considered include marijuana use, which was found to be associated with higher sedation demands by Twardowski et al in 2019 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar 2005 study, Pena et al studied prior endoscopic procedures, history of drug and alcohol use, and nervousness before procedure to predict adverse endoscopic experiences [ 11 ]; similar to Bal et al [ 10 ], they found nervousness and psychotropic drug use to be significantly associated with adverse events. Other interesting patient factors that have been considered include marijuana use, which was found to be associated with higher sedation demands by Twardowski et al in 2019 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar result was obtained in the study conducted by Patel et al [62324] However, in another two studies, midazolam group achieved desired RSS (3–4) significantly earlier than patients in dexmedetomidine group, while no difference is seen between clonidine and midazolam group. [2526] We have used bolus dose (0.04 mg/kg) of midazolam in all the three groups, which could have acted synergistically with dexmedetomidine and clonidine to achieve the desired RSS faster. In our study, the time to achieve RSS ≥2 by Group D was 5.53 ± 0.74, which is similar to the result obtained by Cattano et al [2] Among α2 agonist, Group D took lesser time to achieve target RSS as compared to Group C, as dexmedetomidine is 8 times more specific for α2 receptors, especially for 2A subtype, thus making it a more effective sedative agent as compared to clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular response to the procedure and intubation was more favorable in Groups D and C as compared to Group M. We found consistent decrease in HR and MAP during a bolus infusion of 10 min and less intubation response. [7102629] The lower HR in Group D and Group C than Group M can be explained on the basis of hemodynamic effects of dexmedetomidine and clonidine as these drugs cause a decrease in noradrenaline release and diminish centrally mediated sympathetic tone. [30] Intubation stress response was also diminished in Group D and C, which is explained by the property of attenuation of sympathetic response of intubation by α2 agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clonidine and remifentanil have been used and studied in the setting of controlled hypotension ( Wawrzyniak, Kusza & Cywinski, 2014 ; Miłoński et al, 2013 ; Mohseni & Ebneshahidi, 2011 ; Marchal et al, 2001 ; Lee et al, 1999 ; Hackmann et al, 2003 ; Yun, Kim & Kim, 2015 ; Cardesin et al, 2015 ). These drugs decrease blood loss by decreasing the blood pressure and, more specifically, the cardiac output.…”
Section: Discussionmentioning
confidence: 99%